WFA-labeled perineuronal nets in the macaque claustrum. Issue 1 (1st January 2018) - Pletikos, Mihovil; Rockland, Kathleen S.
ABSTRACT: Background : The claustrum (CLA) has been discussed as central to integrated conscious percepts, although recent evidence has emphasized a role in detecting sensory novelty or in amplifying correlated cortical inputs. Objective : We report that many neurons in the macaque CLA are ensheathed in perineuronal nets (PNNs), which contribute to synaptic stability and enhance neuronal excitability, among other properties. Design : We visualized PNNs by W isteria floribunda agglutinin (WFA) immunohistochemistry, and quantified these in comparison these to parvalbumin+ (PV) subsets and total neurons. Results : PNNs ensheath about 11% of the total neurons. These are a range of large, medium, and small neurons, likely corresponding to PV+ and/or other inhibitory interneurons. The PNNs were themselves heterogeneous, consisting of lattice-like, weakly labeled, and diffuse subtypes, and showed some regional preference for the medial CLA. Conclusion : The abundant neuronal labeling by PNNs in the CLA suggests an important and nuanced role for inhibition, consistent with recent physiological studies of claustrocortical circuitry. For comparison, diversified inhibition in the reticular nucleus of the thalamus (a pan-inhibitory nucleus, with extensive cortical input) exerts a spectrum of control at different local and global spatiotemporal scales. Further investigation of PNN+ neurons in the macaque CLA offers a potentially important new approach to CLA function, relevant to the human brain both in normal and diseased conditions.